Towards increasing web application development productivity through object-oriented framework - Nuruzzaman, Mohd; Hussain, Azham; Mohamad Tahir, Hatim (International Association of Computer Science and Information Technology Press (IACSIT), 2013)
Software development remains complex, expensive and risky.Thus, the need for reusability has become obvious.Through reusability web developers/engineers can save countless hours and millions of dollars in development cost. Object-oriented (OO) framework mechanism provides a new vehicle for reuse and enables web engineers to customize or reuse various aspects in web engineering such as customizing one or more elements of user interface, automatically generate event handlers, data handlers or related data elements based on changes made by them.The OO framework mechanism includes tags and scripts that predefine some generic web application activities and a common programming interface for generating a framework customization environment. This study provides a novel solution to produce high quality web applications within a shortest development timeframe through the means of customization, reusability, extensibility and flexibility.At the end, this study will conduct a comprehensive evaluation on the proposed OO framework. Building on previous works, this study emphasized the reuse of design, code and testing as a tool to uncover strengths and weaknesses of the OO framework for dynamic web engineering.